From the Bush to the Village in Northern Saskatchewan: Contrasting CCF Community Development Projects - Quiring, David (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2006)
AbstractThe election of the CCF in 1944 brought rapid change for the residents of northern Saskatchewan. CCF initiatives included encouraging northern aboriginals to trade their semi-nomadic lifestyles for lives in urban settings. The establishment of Kinoosao on Reindeer Lake provides an example of how CCF planners established new villages; community development processes excluded local people. Yet, in spite of considerable resistance, various incentives and coercive measures resulted in the movement of nearly all northerners to permanent settlements. A very different community development project unfolded at Cole Bay in the 1960s. Early CCF urbanization projects had missed several hundred Métis people in the remote Canoe Lake area of northwest Saskatchewan. The creation of the Cold Lake Air Weapons Range in the 1950s resulted in the Métis losing access to much of their traditional land. With guidance from Ray Woollam, an influential CCF official, local people actively participated in designing and building their community. This study of urbanization in northern Saskatchewan adds to the literature on relocations and community development in northern Canada and beyond. In addition, it provides information about CCF aboriginal and northern policies.